Pengaruh Kompetensi, Independensi, dan Motivasi Auditor Internal terhadap Efektivitas Struktur Pengendalian Internal Pada Kalla Group - nurbayani, nurbayani; Muliana, Muliana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2019)
This research aims to analyze and prove  the effect of competency, independecy and motivation intern auditor on the effectiveness  structure of internal control  on the group kalla.  The sample of research consists of 30  respondens they are intern auditor of kalla group. The research data uses kuesioner.  The analysis technique of research data uses multiple regretion analysis. The empirical results find that  kompetence, can determine effectiveness of internal control, but independece and motivation canâ??t determine effectiveness of internal control on the group kalla